Optimization model and development of power estimation in photovoltaics for self-load consumption - Yosefa Hutajulu, Olnes; Dwi Waluyo, Bakti; Dodi Suryanto, Eka; Haryanto Sinaga, Denny; Suwarno, Suwarno; Indra Cahyadi, Catra; Junaidi, Agus (Institute of Advanced Engineering and Science, 2025)
The Indonesian government's initiative to meet a renewable electricity supply 2050 of around 100% and its ecological benefits, has an impact on the big challenge where the increasing number of photovoltaic (PV) systems due to high power input and risks to electricity network security conditioned sunny weather for a long time. This research aims to provide predictable power output for network operators, thereby enabling longer planning periods and increasing the protection of the national operational network. Independent consumption by household consumers will impact household energy behavior and affect the security of the electricity network. Consumption itself provides an incentive to increase the cost of energy use which will be much higher than the compensation received, so software is needed which can support PV system prediction patterns. This pattern will close the gap in software development in the process of implementing optimization and configuration based on PV estimates. The consumption planning optimization algorithm itself validates the predetermined scenario optimization process. This research contributes to the efficiency and stability of energy use in households.